PENGARUH PERPUTARAN MODAL KERJA, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP PROFITABILITAS PERUSAHAAN ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA - B11108066, Viranti (Jurnal Manajemen Update, 2012)
Profitability is an indicator of the performance and ability of the enterprise to take advantage of all the assets owned for profit. An assessment of the profitability of the enterprise can be measured by the Return on Investment (ROI), the rate of return on investment in assets. This study examines the effect of financial ratios that include working capital turnover ratio (working capital turnover), firm size (natural logarithm of total assets), and leverage (Debt to Total Assets Ratio) to profitability (ROI) in registered tobacco companies in BEI. The purpose of this study was to determine the effect of working capital turnover, firm size and leverage either simultaneously or partially on the profitability of the cigarette industry listed on the Stock Exchange, as well as to determine which of these ratios that have a dominant influence on profitability. This research uses documentation techniques, and literature as well as using multiple regression analysis, t test, F test and the beta coefficient as a method of data analysis. Keywords : working capital turnover ratio, firm size, leverage ratio